RESERACH ON FATIGUE BEHAVIOUR COMPARISON OF ALUMINUM RIVETED JOINT AND FRICTION STIR WELDING JOINT - ZHANG YanJun; LI XiaoPeng (Jixie qiangdu)
S-N curves of 2524-T3 parental material,FSW joint,riveted joint were obtained by fatigue test of FSW comparative specimens. Result revealed that firstly fatigue cracks in FSW joints were mostly initiated from bottom of the weld seam. Secondly,fatigue behavior of thin plate was slightly better than that of thick plate. Finally,fatigue behavior of FSW joint was significantly better than that of riveted joint. S-N curves for variable thicknesses and stress ratios were fitted,which provided correlative data for application of FSW technology to aircraft structures.